(untitled) (Docentes 2.0 Journal, 2015)
The country has a model of institutional organization of the dual-type tertiary sector articulated on the basis of a free public education, traditionally based on high quality standards derived from the selective nature, teacher salaries, postgraduate weight and An orientation towards research. A public sector model oriented under the pattern of American Universities focused on specialized and market-oriented responses under a German-type research model. Both in access to undergraduate and postgraduate studies there are high levels of academic selection, reaffirmed by the gratuity and the high quality standards in turn associated with the structure of labor remuneration.